Пошаговое объяснение:
по теореме Виета
-1*-3=3 (это будет с)
-1+-3=-4 (это -б)
получается
х^2 + 4х + 3=0
Система :
{х/у=(11-у)/(14-х),
{х^2+у^2+(11-у)^2+(14-х)^2=221,
{х(14-х)=у(11-у)
{х^2+у^2+121-22у+у^2+196-28х+х^2=221
{14х-х^2=11у-у^2
{2х^2+2у^2-22у-28х=-96 ¦ :2,
{14х-х^2=11у-у^2
{х^2+у^2-11у-14х=-48,
{у^2-х^2+14х-11у=0 (1)
{у^2+х^2-14х-11у=-48, (2)
Разность (1)-(2):
-2х^2+28х=48 ¦ :(-2)
х^2-14х+24=0,
х1=12, х2=2.
Если х= 12, то у(11-у)=12(14-12),
-у^2+11у=24,
у^2-11у+24=0, у=3 и у=8
Если х=2, то у(11-у)=2(14-2),
у^2-11у+24=0, у=3 и у=8.
Пропорция: х/у=(11-у) /(14-х)
12/3=8/2, 12/8=3/2, 2/3=8/12, 2/8=3/12.
Числа в пропорции 2, 3, 8, 12.
х1=-1
х2=-3
х1+х2= -4
х1*х2= 3
х^2+4х-3=0